The asymmetric CFT landscape in D=4, 6, 8 with extended supersymmetry. Issue 3 (20th March 2017) - Blumenhagen, Ralph; Fuchs, Michael; Plauschinn, Erik
Abstract : The authors study asymmetric simple‐current extensions of Gepner models in dimensions D = 4; 6; 8 with at least eight supercharges in the right‐moving sector. The models obtained in an extensive stochastic computer search belong to a small number of different classes. These classes can be categorized as dimensional reductions, asymmetric orbifolds with ( − 1 ) F L, extra gauge enhancement and as coming from the super Higgs‐effect. Models in the latter class are particularly interesting, as they may correspond to non‐geometric flux compactifications. Abstract : We study asymmetric simple‐current extensions of Gepner models in dimensions D = 4, 6, 8 with at least eight supercharges in the right‐moving sector. The models obtained in an extensive stochastic computer search belong to a small number of different classes. These classes can be categorized as dimensional reductions, asymmetric orbifolds with ( − 1 ) F L, extra gauge enhancement and as coming from the super Higgs‐effect. Models in the latter class are particularly interesting, as they may correspond to non‐geometric flux compactifications.